2007
DOI: 10.1080/07370010709336584
|View full text |Cite
|
Sign up to set email alerts
|

Child Health Needs of Rural Alabama Latino Families

Abstract: This article presents findings from a study that used focus group methodology to identify perceptions of Latino parents living in rural Alabama related to their children's health needs. Sixteen focus groups were held with a total of 89 parents (54 mothers and 35 fathers). The groups were led by native Spanish speakers, and group meetings were tape recorded. The main themes that emerged related to (a) what children need to be healthy, (b) common children's health problems, (c) what we do when children are ill, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The most common alternative healthcare practice was chamomile tea, boiled epazote leaves to treat fever, cough, upper respiratory tract infections (URIs), diarrhea, vomiting, and teething. These alternative healthcare practice medicines have also been reported by other researchers for similar uses (Harrison & Scarinci, ; Taveras et al., ). Other alternative healthcare practices documented by Crocetti et al () for treating fever include applying alcohol on the feet or other parts of the body; placing potato slices in axilla area; and onion, salt, and liquor on their feet.…”
Section: Alternate Healthcare Practicessupporting
confidence: 76%
See 1 more Smart Citation
“…The most common alternative healthcare practice was chamomile tea, boiled epazote leaves to treat fever, cough, upper respiratory tract infections (URIs), diarrhea, vomiting, and teething. These alternative healthcare practice medicines have also been reported by other researchers for similar uses (Harrison & Scarinci, ; Taveras et al., ). Other alternative healthcare practices documented by Crocetti et al () for treating fever include applying alcohol on the feet or other parts of the body; placing potato slices in axilla area; and onion, salt, and liquor on their feet.…”
Section: Alternate Healthcare Practicessupporting
confidence: 76%
“…Chamomile tea Infant Vomiting, allergic reaction Diarrhea, vomiting, colic, teething (Harrison & Scarinci, 2007;Tavares, Duroussea, & Flores, 2004) Child (Blumenthal, 2003) Fever (Aka* Artemisia absinthium) (Erdemir, 2010) Vomiting (Mabey, 1988) Ginger Child Gastrointestinal irritation (Murray, 2002) a Aka, also known as.…”
Section: Fever Coldsmentioning
confidence: 99%
“…Cough medicine and laxatives were also used for cough and stomach-related symptoms (Mendelson, 2003;Mikhail, 1994). Parents in four studies reported giving their children medications from Mexico (Foronda & Waite, 2008;Grigg et al, 2013;Harrison & Scarinci, 2007;Mikhail, 1994). Reasons for this practice included the high cost of medications in the United States and the availability of antibiotics over the counter in Latin American countries (Grigg et al, 2013;Harrison & Scarinci, 2007).…”
Section: Popular Sector: Self-management Of Illnessmentioning
confidence: 99%
“…Parents in four studies reported giving their children medications from Mexico (Foronda & Waite, 2008;Grigg et al, 2013;Harrison & Scarinci, 2007;Mikhail, 1994). Reasons for this practice included the high cost of medications in the United States and the availability of antibiotics over the counter in Latin American countries (Grigg et al, 2013;Harrison & Scarinci, 2007). Three studies reported the use of aspirin for fever, with one noting 23% of mothers using aspirin (Foronda & Waite, 2008;Mikhail, 1994;Taveras et al, 2004).…”
Section: Popular Sector: Self-management Of Illnessmentioning
confidence: 99%
See 1 more Smart Citation